Izbor lokacije avtobusne postaje na podlagi hibridnega modela večkriterijskega odločanja v Uşaku v Turčiji - Kahraman, Sümeyye (Urbani izziv, 2025)
The location of a bus terminal is crucial for efficient urban transportation and sustainable urban mobility. The location determines visitors’ access to the city and safe, accessible, and economical transportation options. It also affects residents’ access to employment, education, and health services and their efficiency, shaping the city’s overall socioeconomic wellbeing. This study determines the optimal location for a new bus terminal in Uşak, Turkey, considering efficient operation of the city’s transportation systems. The methodology employs a hybrid multicriteria decision-making model that evaluates twenty criteria, integrates the needs of residents and local authorities, and draws on urban transportation planning expertise for a comprehensive assessment of accessibility. The AHP method was used to assign weights to twenty evaluation criteria, and seven alternative areas were ranked using the MOOSRA, ARAS, and VIKOR methods. The findings revealed the most suitable location, demonstrating the robustness of the model and its applicability in urban planning.
Keywords: ARAS; avtobusna postaja; bus terminal; izbor lokacije; location selection; MOOSRA; multicriteria analysis; večkriterijska analiza; VIKOR